Ortorexia nervosa e exercício físico: uma revisão narrativa - COSTA, Jeiel Melo da (2023)
Orthorexia nervosa is characterized by a pathological obsession with healthy eating, in which the goal of those who suffer from this condition is to reach a state of optimum health. In this sense, the practice of physical exercise provides several health benefits, in addition, its relationship with the psychopathology of other eating disorders is well known. Therefore, studies have sought to investigate a possible relationship between orthorexia nervosa and physical exercise, however, this association has been investigated recently, so it is necessary to obtain a better understanding of this theme. The aim of this study is to present a narrative review of the literature on the relationship between orthorexia nervosa and physical exercise. Searches were carried out for articles in the PUBMED, SCIELO, GOOGLE SCHOLAR and CAPES databases. After analysing the studies, a positive association between orthorexia nervosa and higher frequency of physical exercise was evidenced in several samples used in the researches, in addition, some studies revealed the presence of dysfunctional behavior related to physical exercise in individuals with orthorexia nervosa, presenting characteristics of obsession, compulsion and rigidity. These results demonstrate that physical exercise appears to play a role in the psychopathology of orthorexia nervosa. However, due to the methodological limitations of some studies included in this research, it is not possible to know to what extent these findings are relevant to designate physical exercise as one of the indicatives of orthorexia nervosa or even to establish a causal relationship between both factors. It is suggested that future studies on this topic use more reliable questionnaires, aiming to increase the degree of reliability of the results obtained.